Numerical simulation on NOX emissions in a municipal solid waste incinerator. (1st October 2019) - Hu, Zhifeng; Jiang, Enchen; Ma, Xiaoqian
Abstract: The simulations of combustion and NOX emissions process are conducted by computational fluid dynamics method with comprehensive physical and chemical models in a municipal solid waste incinerator. This study focused on the effects of primary NOX control methods (different loads, over fire air, the ratios of secondary air and over fire air) and secondary NOX control methods (selective non-catalytic reduction process) on NOX emission and combustion characteristic. Results showed that the moisture evaporation rate, volatile release rate, char burning rate, temperature and the strength of flow velocity decreased as decreasing the operating load. However, the NOX emission of furnace outlet increased from 273.18 mg/Nm 3 to 602.10 mg/Nm 3 . 100% operating load was the best condition to obtain a lowest NOX emission and a best combustion characteristic among different loads. In addition, the combustion strategy combining secondary air and over fire air could improve the combustion performance and reduce NOX emission. Further, a higher over fire air ratio was conducive to the formation of strong swirl flow and the enhancement of flow velocity strength in the flue. The optimal over fire air ratio was 31%–35% with NOX emission of 267.05 mg/Nm 3 to 273.18 mg/Nm 3 and residence time of 2.75 s–3.03 s. Moreover, ammonia based selective non-catalytic reduction process, better than urea, achieved a NOX emission of 132.41 mg/Nm 3, a NOX removal efficiency of 51.50% and NH3 slip of 11.08 mg/Nm 3 or 6.71 ppm. The study indicated that the optimal NOX control method was a condition of 100% load, combining with over fire air and 31% and 35% over fire air ratio. Moreover, the best secondary NOX control method was the ammonia based selective non-catalytic reduction process. Highlights: The NOX emission of furnace outlet increased as decreasing the operating load. Operating load, OFA, OFA ratio and SNCR did have an impact on flow velocity strength. OFA affected the combustion characteristics and NOX emission. The optimal OFA ratio was 31%–35% with NOX emission of 267.05–273.18 mg/Nm 3 . Ammonia based SNCR, with a NOX removal efficiency of 51.50%, was better than urea.